Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.13653
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of cyclin B1 in solid tumors: a meta-analysis

Abstract: Cyclin B1 is a key mitotic cyclin in the G2-M phase transition of the cell cycle and is overexpressed in various malignant tumors. Numerous studies have reported contradictory evidences of the correlation between cyclin B1 expression and prognosis in human solid tumors. To address this discrepancy, we conducted a meta-analysis with 17 published studies searched from PubMed and Medline. Cyclin B1 overexpression was significantly associated with poor 3-year overall survival (OS) (OR = 2.05, 95% CI = 1.20 to 3.50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…After 34 studies were excluded according to our including criteria, eventually a total of 12 articles (2080 patients) were included for analysis and evaluation, of which 11 articles [ 14 20 , 22 – 25 ] including 1971 patients were included for analyzing the correlation of positive/high expression of cyclin B1 and OS, 9 studies [ 15 17 , 19 , 21 25 ] including 1253 participants for analyzing the correlation between cyclin B1 and clinicopathological features (Figure 1 ). The excluding reasons were as follows: 32 studies for lack of available data; 1 study [ 26 ] for the definition of positive/high expression did not meet our including criteria; 1 study [ 27 ] was just a review article with no available data. Of the included studies, six were conducted in Japan, three in China, each one in Brazil, Germany and Korea.…”
Section: Resultsmentioning
confidence: 99%
“…After 34 studies were excluded according to our including criteria, eventually a total of 12 articles (2080 patients) were included for analysis and evaluation, of which 11 articles [ 14 20 , 22 – 25 ] including 1971 patients were included for analyzing the correlation of positive/high expression of cyclin B1 and OS, 9 studies [ 15 17 , 19 , 21 25 ] including 1253 participants for analyzing the correlation between cyclin B1 and clinicopathological features (Figure 1 ). The excluding reasons were as follows: 32 studies for lack of available data; 1 study [ 26 ] for the definition of positive/high expression did not meet our including criteria; 1 study [ 27 ] was just a review article with no available data. Of the included studies, six were conducted in Japan, three in China, each one in Brazil, Germany and Korea.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that CCNB1 is required for cell cluster rotation (Figure ). A previous meta‐analysis showed that the contribution of CCNB1 expression in solid tumors to prognosis is controversial . Western blot and mRNA expression analyses indicated that the elevated expression was negatively associated with lymph node metastasis, distant metastasis stage and TNM stage in CRC .…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis showed that the contribution of CCNB1 expression in solid tumors to prognosis is controversial. 1,51,52 Western blot and mRNA expression analyses indicated F I G U R E 8 Summary of the in vitro model system for collective cell migration at the invasive front. CCNB1, cyclin B1 that the elevated expression was negatively associated with lymph node metastasis, distant metastasis stage and TNM stage in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that overexpression of cyclinB1 was associated with poor survival in patients with most types of solid tumors, suggesting that the expression of cyclinB1 is an important parameter for prognosis in this setting. 11 It was found that the expression of cyclinB1 was higher in malignant specimens than in benign cases, suggesting that cyclinB1 can be used as an effective marker for the differentiation of benign and For personal use only. malignant thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%